Assessment of past and present soil conservation initiatives in Nigeria, West Africa - Junge, B.; Deji, O.F.; Abaidoo, Robert C.; Chikoye, David; Stahr, Karl (Tropentag, 2007)
Soil conservation has a long tradition in West Africa and various on-farm and off-farm soil conservation technologies already exist. An extensive literature review has shown that mulching, crop management and conservation tillage are adequate measures for combating soil degradative processes such as soil loss in the savanna of Nigeria. Most farmers are in general aware of environmental problems but adopt only technologies which are compatible with the present farming system and whose costs of installation and maintenance are low. As education and training on soil conservation seem to increase the adoption of appropriate technologies, the work of extension agencies is important.